A five-parameter fractional derivative temperature spectrum model for polymeric damping materials. (September 2020) - Zhang, Heng; Li, Shiqi; Zhang, Zhenli; Luo, Hanbin; Wang, Yue
Abstract: To capture viscoelastic behavior of polymeric damping materials based on limited dynamic mechanical analysis tests, a simple fractional temperature spectrum model representing the viscoelastic materials is proposed in this paper and experimental tests aims at stressing the validity of the model. The storage modulus, the loss modulus, and the loss factor, are established based on the five-parameter fractional derivative model and the time–temperature superposition principle. The dynamic mechanical tests of two polymeric materials are carried out to verify this temperature spectrum model. Results indicate a good agreement between the temperature spectrum model and experimental tests at various temperature conditions. Furthermore, thermodynamic coupling of the viscoelastic material is investigated by temperature rise calculation and vibration experiment test. Comparison analysis shows that the temperature rise model can simulate the temperature rise process for the shear vibration of the constrained damping, which provide references for the damping capability, thermal damage and failure of viscoelastic material. Highlights: Viscoelastic behavior of polymeric damping materials was investigated. A fractional temperature spectrum model was established. Experimental tests aimed at stressing the validity of the model. A calculation method was proposed to predict thermodynamic coupling process.